Measurements of Human Middle- and Inner-Ear Mechanics With Dehiscence of the Superior Semicircular Canal - Chien, Wade (2007)
OBJECTIVES: (1) To develop a cadaveric temporal-bone preparation to study the mechanism of hearing loss resulting from superior semicircular canal dehiscence (SCD) and (2) to assess the potential usefulness of clinical measurements of umbo velocity for the diagnosis of SCD. BACKGROUND: The syndrome of dehiscence of the superior semicircular canal is a clinical condition encompassing a variety of vestibular and auditory symptoms, including an air-bone gap at low frequencies. It has been hypothesized that the dehiscence acts as a “third window” into the inner ear that shunts acoustic energy away from the cochlea at low frequencies, causing hearing loss. METHODS: Sound-induced stapes, umbo, and round-window velocities were measured in prepared temporal bones (n = 8) using laser-Doppler vibrometry (1) with the superior semicircular canal intact, (2) after creation of a dehiscence in the superior canal, and (3) with the dehiscence patched. Clinical measurements of umbo velocity in live SCD ears (n = 29) were compared with similar data from our cadaveric temporal-bone preparations. RESULTS: An SCD caused a significant reduction in sound-induced round-window velocity at low frequencies, small but significant increases in sound-induced stapes and umbo velocities, and a measurable fluid velocity inside the dehiscence. The increase in sound-induced umbo velocity in temporal bones was also found to be similar to that measured in the 29 live ears with SCD. CONCLUSION: Findings from the cadaveric temporal-bone preparation were consistent with the third-window hypothesis. In addition, measurement of umbo velocity in live ears is helpful in distinguishing SCD from other otologic pathologies presenting with an air-bone gap (e.g., otosclerosis).